Effect of ellagic acid on growth and some antioxidant parameters in scaly carp (Cyprinus carpio) - Eksen, Tuncay; Yonar, Serpil Mise (Ege Univ, Fac Fisheries, 2021)
In the present study, it was investigated the effects of various levels of dietary ellagic acid on growth performance and antioxidant status in scaly carp (Cyprinus carpio). Fish were fed with the control diet and three different experimental diets containing three graded levels of ellagic acid (50, 100 and 200 mg kg(-1) diet) for 60 days. On 30th and 60th days of experiment, the growth performance [live weight gain, relative growth and specific growth rate] and oxidant/antioxidant parameters [malondialdehyde level, catalase and glutathione-S-transferase activities and reduced glutathione level] were analysed. There was no statistically significant difference in the live weight gain, relative growth and specific growth rates of the control and ellagic acid treated groups (p > 0.05). When compared to the control group, the liver and kidney malondialdehyde levels of ellagic acid treated groups were significantly decreased (p < 0.05). The liver and kidney catalase and glutathione-S-transferase activities and reduced glutathione levels of ellagic acid treated groups were significantly increased when compared to the control group (p < 0.05). It was concluded that ellagic acid can be used as an antioxidant in fish.
Keywords: Antioxidant; growth parameters; ellagic acid; oxidative stress; carp